THE SIGNIFICANCE OF RUMI’S PHILOSOPHY IN ELEVATING THE WORLDVIEW OF THE YOUNGER GENERATION - Samatov Jonmurod (Western European Studies, 2025)
Rumi’s philosophy holds great significance in shaping and elevating the worldview of the younger generation. In today’s fast-paced world, where technological advancements and globalization have led to both progress and social challenges, his teachings provide essential guidance for spiritual growth, self-awareness, and inner peace. This article explores the significance of Jalaluddin Rumi's philosophical and Sufi views in the spiritual development of youth
Keywords: Masnavi; Rumi; younger generation; spiritual growth